Nonclassical Symmetry Analysis of Boundary Layer Equations - Rehana Naz; Mohammad Danish Khan; Imran Naeem (Journal of Applied Mathematics)
The nonclassical symmetries of boundary layer equations for two-dimensional and radial flows are considered. A number of exact solutions for problems under consideration were found in the literature, and here we find new similarity solution by implementing the SADE package for finding nonclassical symmetries.